2021
DOI: 10.3390/insects12090788
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Related Wolbachia across Unrelated Leaf-Mining Diptera

Abstract: The maternally inherited endosymbiont, Wolbachia pipientis, plays an important role in the ecology and evolution of many of its hosts by affecting host reproduction and fitness. Here, we investigated 13 dipteran leaf-mining species to characterize Wolbachia infections and the potential for this endosymbiont in biocontrol. Wolbachia infections were present in 12 species, including 10 species where the Wolbachia infection was at or near fixation. A comparison of Wolbachia relatedness based on the wsp/MLST gene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…1, and D. isaea were identical and belong to Wolbachia Supergroup A. This wsp sequence is identical to the wsp sequence of L. sativae (wLsatC) from Vietnam (Xu et al, 2021a). The Wolbachia wsp sequences of H. varicornis and Opius sp.…”
Section: Endosymbiont Detectionsmentioning
confidence: 68%
See 2 more Smart Citations
“…1, and D. isaea were identical and belong to Wolbachia Supergroup A. This wsp sequence is identical to the wsp sequence of L. sativae (wLsatC) from Vietnam (Xu et al, 2021a). The Wolbachia wsp sequences of H. varicornis and Opius sp.…”
Section: Endosymbiont Detectionsmentioning
confidence: 68%
“…There is only a single base pair difference between the Wolbachia wsp sequences of H. varicornis from Fiji (this study where all 11 specimens were infected) and Japan (NCBI: AB231470.1/AB231471.1) (Tagami et al, 2006). Additionally, the Wolbachia wsp sequence of H. varicornis from Fiji is identical to the wsp sequence of L. bryoniae from Japan (wLbryB) (Tagami et al, 2006;Xu et al, 2021a). The Wolbachia wsp sequence of H. varicornis from Australia (this study) is three base pairs different to the wsp sequence of L. bryoniae (wLbryA) from the Netherlands (Xu et al, 2021a).…”
Section: Endosymbiont Detectionsmentioning
confidence: 76%
See 1 more Smart Citation
“…As a result, the population of Liriomyza spp. will increase gradually in a geographical environment with more different host plants (Tran et al 2007b;Xu et al 2021). This study showed that the population abundance of Liriomyza spp.…”
Section: Discussionmentioning
confidence: 79%
“…As species of Liriomyza have similar external morphology, taxonomic identification of L. sativae samples was confirmed by both morphological identification (by Dr. Mallik Malipatil, Agriculture Victoria, AgriBio, La Trobe University, Bundoora, Australia) and barcodes based on mitochondrial cytochrome c oxidase subunit I (CO1). For barcoding, legs of flies were taken from specimens for Chelex DNA extraction with protocols following previous work except in 70 μl of 5% Chelex 100 resin (Bio‐Rad Laboratories, Gladesville, NSW, Australia) (Coquilleau et al, 2021 ; Xu, Coquilleau et al, 2021 ; Xu, Ridland et al, 2021 ). The criteria for assigning CO1 haplotypes were based on BLAST similarity in NCBI (Johnson et al, 2008 ) with 100% similarity being used to link to existing haplotypes, and assignment to L. sativae clades defined by a similarity threshold of <2.5% (Scheffer & Lewis, 2005 ).…”
Section: Methodsmentioning
confidence: 99%